Review of the genus Termioptycha Meyrick, 1889 (Lepidoptera, Pyralidae) from China, with descriptions of four new species - Rong, Hua; Wang, Yiping; Li, Houhun (Zootaxa, 2017)
The genus Termioptycha Meyrick, 1889 from China is reviewed. Among the ten species studied, T. longiclavata sp. nov., T. longispina sp. nov., T. nigrimacularis sp. nov. and T. cornutitrifurca sp. nov. are described as new; T. conjuncta (Warren, 1896), comb. rev. is re-allocated in this genus from Salma Walker, 1863; and T. conjuncta and T. eucarta (Felder & Rogenhofer, 1875) are newly recorded in China. Photographs of adults and genitalia are provided. A key to the ten species in China based on male genitalia is provided.